Deep eutectic solvent-catalyzed Meyer–Schuster rearrangement of propargylic alcohols under mild and bench reaction conditions. Issue 96 (20th November 2020) - Ríos-Lombardía, Nicolás; Cicco, Luciana; Yamamoto, Kota; Hernández-Fernández, José A.; Morís, Francisco; Capriati, Vito; García-Álvarez, Joaquín; González-Sabín, Javier
Abstract : Faster, milder, greener…better! The Meyer–Schuster rearrangement is disclosed for the first time in a deep eutectic solvent, namely FeCl3 ·6H2 O/glycerol (3 : 1), enabling the reaction at room temperature, under air and with short reaction times. Abstract : The Meyer–Schuster rearrangement of propargylic alcohols into α, β-unsaturated carbonyl compounds has been revisited by setting up an atom-economic process catalyzed by a deep eutectic solvent FeCl3 ·6H2 O/glycerol. Isomerizations take place smoothly, at room temperature, under air and with short reaction times. The unique solubilizing properties of the eutectic mixture enabled the use of a substrate concentration up to 1.0 M with the medium being recycled up to ten runs without any loss of catalytic activity.